Contrast enhanced ultrasound in mixed hepatocellular cholangiocarcinoma: case series and review of the literature - Dong, Yi; Teufel, Andreas (Digestive and liver disease, 2018)
Background: Mixed hepatocellular cholangiocarcinoma is a rare form of primary liver cancer. Aims: The aim of this study is to report the results of the use of contrast enhanced ultrasound in a series of patients with confirmed mixed hepatocellular cholangiocarcinoma and to provide an updated literature review. Methods: Between January 2012 and October 2016, 25 Asian patients with confirmed mixed hepatocellular cholangiocarcinoma were included in this bicentric retrospective analysis. Clinical data as well recorded images of a standardized conventional B-mode ultrasound and contrast-enhanced ultrasound examination were interpreted by two blinded, independent, experienced radiologists in consensus. Results: All mixed hepatocellular cholangiocarcinoma lesions were heteroechoic on B-mode ultrasound, with ill-defined margins and irregular shapes. Arterial phase hyperenhancement was present in all 25 patients. Late-phase washout and hypoenhancement was present in 24/25 (96%) patients. However, rim-enhancement and early wash-out (which are common in cholangiocellular carcinoma) were found in over 60% of the cases. Conclusion:Contrast-enhanced ultrasound demonstrated findings not typical for HCC in a large proportion of patients with confirmed mixed hepatocellular cholangiocarcinoma. Therefore, histological confirmation is crucial, especially in lesions with atypical findings.